Parent-Reported Use of Pediatric Primary Care Telemedicine: Survey Study - Kristin N Ray; Samuel R Wittman; Sarah Burns; Tran T Doan; Kelsey A Schweiberger; Jonathan G Yabes; Janel Hanmer; Tamar Krishnamurti (JMIR Publications, 2023)
BackgroundTelemedicine delivered from primary care practices became widely available for children during the COVID-19 pandemic. ObjectiveFocusing on children with a usual source of care, we aimed to examine factors associated with use of primary care telemedicine. MethodsIn February 2022, we surveyed parents of children aged ≤17 years on the AmeriSpeak panel, a probability-based panel of representative US households, about their children's telemedicine use. We first compared sociodemographic factors among respondents who did and did not report a usual source of care for their children. Among those reporting a usual source of care, we used Rao-Scott F tests to examine factors associated with parent-reported use versus nonuse of primary care telemedicine for their children. ResultsOf 1206 respondents, 1054 reported a usual source of care for their children. Of these respondents, 301 of 1054 (weighted percentage 28%) reported primary care telemedicine visits for their children. Factors associated with primary care telemedicine use versus nonuse included having a child with a chronic medical condition (87/301, weighted percentage 27% vs 113/753, 15%, respectively; P=.002), metropolitan residence (262/301, weighted percentage 88% vs 598/753, 78%, respectively; P=.004), greater internet connectivity concerns (60/301, weighted percentage 24% vs 116/753, 16%, respectively; P=.05), and greater health literacy (285/301, weighted percentage 96% vs 693/753, 91%, respectively; P=.005). ConclusionsIn a national sample of respondents with a usual source of care for their children, approximately one-quarter reported use of primary care telemedicine for their children as of 2022. Equitable access to primary care telemedicine may be enhanced by promoting access to primary care, sustaining payment for primary care telemedicine, addressing barriers in nonmetropolitan practices, and designing for lower health-literacy populations.